La deuxieme Republique Rwandaise: Evolution, bilan et perspectives - Reyntjens, Filip (Afrika Focus, 1986)
This paper provides a short survey and assessment of the political evolution of Rwanda since the inception of the Second Republic in 1973. After a period of de facto rule the country returned to constitutional government in 1978. A single party, the Revolutionary National Movement for the Development, had already been created by the military in 1975. The paper examines the constitution, the organisation of elections, political conflict and the respect for human rights and the rule of law. While the regime has achieved considerable successes, the paper argues that its level of institutionalisation remains limited and that its stability and achievements are essentially due to the personality of President Habyarimana. KEYWORDS : civilianisation, constitutional law, political change, Rwanda